2020
DOI: 10.1101/2020.12.18.423363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omic profiling reveals widespread dysregulation of innate immunity and hematopoiesis in COVID-19

Abstract: Our understanding of protective vs. pathologic immune responses to SARS-CoV-2, the virus that causes Coronavirus disease 2019 (COVID-19), is limited by inadequate profiling of patients at the extremes of the disease severity spectrum. Here, we performed multi-omic single-cell immune profiling of 64 COVID-19 patients across the full range of disease severity, from outpatients with mild disease to fatal cases. Our transcriptomic, epigenomic, and proteomic analyses reveal widespread dysfunction of peripheral inna… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 148 publications
9
98
0
Order By: Relevance
“…This enrichment in neutrophil signatures has been shown to be independent of lung injury, age, gender and underlying co-morbidities (78), suggesting that rather than simply representing a marker of severe lung inflammation, neutrophils contribute to the immunopathology that underpins the onset of COVID-19 pneumonia (78). Akin to the findings reported in whole blood (17,18,21), heterogeneity has also been reported in the pulmonary neutrophil pool (48,78). Wauters et al clustered BALF residing neutrophils into five distinct phenotypes and found the frequency of both "progenitor" and "inflammatory mature" neutrophils were significantly higher in samples from mild/critical COVID-19 patients when compared to subjects with non-COVID-19 pneumonia (78).…”
Section: Analysis Of Balfmentioning
confidence: 83%
See 3 more Smart Citations
“…This enrichment in neutrophil signatures has been shown to be independent of lung injury, age, gender and underlying co-morbidities (78), suggesting that rather than simply representing a marker of severe lung inflammation, neutrophils contribute to the immunopathology that underpins the onset of COVID-19 pneumonia (78). Akin to the findings reported in whole blood (17,18,21), heterogeneity has also been reported in the pulmonary neutrophil pool (48,78). Wauters et al clustered BALF residing neutrophils into five distinct phenotypes and found the frequency of both "progenitor" and "inflammatory mature" neutrophils were significantly higher in samples from mild/critical COVID-19 patients when compared to subjects with non-COVID-19 pneumonia (78).…”
Section: Analysis Of Balfmentioning
confidence: 83%
“…Using a range of analytical approaches that have included single cell RNA-seq (scRNA-seq), high-dimensional flow cytometry and mass cytometry, a number of studies have reported marked differences in the composition of the circulating neutrophil pool between COVID-19 patients of differing disease severities (18,29,48,49,(122)(123)(124)(125). Supporting the idea that distinct innate immune responses underlie the different clinical trajectories of COVID-19, an accumulation of LDNs is emerging as a signature of severe disease (18,21).…”
Section: Neutrophil Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…A strong hyperactivation phenotype in peripheral PMNs has already been directly associated with severe cases of COVID-19, including increased phagocytosis, degranulation and chemotaxis, and increased expression of genes involved in pro-inflammatory cytokine release. Within these severe cases, the emergence of an immature PMN population, characteristic of emergency myelopoiesis, was the main difference observed between the immune responses in fatal and non-fatal cases of COVID-19 (73). NET formation in tissue injury and thrombotic complications are additional pathogenic mechanisms whereby circulating PMNs can lead to more severe COVID-19 (6,28,31,32,34).…”
Section: Periodontal Disease-induced Immunopathology and Covid-19mentioning
confidence: 99%